1986
DOI: 10.1185/03007998609111098
|View full text |Cite
|
Sign up to set email alerts
|

Pipothiazine palmitate: a versatile, sustained-action neuroleptic in psychiatric practice

Abstract: A study lasting 1 year assessed the effectiveness and tolerance of depot neuroleptic treatment with pipothiazine palmitate in 52 patients suffering from schizophrenia or related conditions (17 acute and 35 chronic). A 100 mg dose was given to 31 patients and 50 mg to 21 patients: 40 patients received injections 4-weekly, 8 patients 3-weekly and 4 patients 2-weekly. Duration of treatment ranged from 3 to 12 months, involving a total of 347 patient-months. The significant improvement produced by pipothiazine pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…38 Later trials found doses of 50-200 mg every 4 weeks to be adequately effective. 39,40 Zuclopenthixol decanoate is initiated with a test dose of 100 mg and maintenance doses vary from 200 mg every 4 weeks to 600 mg a week. In an open dose-reduction study of 23 patients, the minimum effective dose was shown to be, on average, 200 mg every 2 weeks (range 60-400 mg).…”
Section: Dose and Administrationmentioning
confidence: 99%
“…38 Later trials found doses of 50-200 mg every 4 weeks to be adequately effective. 39,40 Zuclopenthixol decanoate is initiated with a test dose of 100 mg and maintenance doses vary from 200 mg every 4 weeks to 600 mg a week. In an open dose-reduction study of 23 patients, the minimum effective dose was shown to be, on average, 200 mg every 2 weeks (range 60-400 mg).…”
Section: Dose and Administrationmentioning
confidence: 99%